The No Child Left Behind Act and the Black-White Achievement Gap - Hamadouche, FATIMA (Journal of Human Sciences, 2016)
The present article probes into the No Child Left Behind Act (NCLB) of 2002 and appraises its impact on closing the black-white achievement gap in American public education. Aiming at boosting academic achievement in schools across the United States, rising the performance of underprivileged students to the level of their more affluent counterparts and magnetizing qualified professionals to teach in every classroom, the NCLB is in effect the end product of a series of noteworthy embryonic and evolving key federal educational policies and reforms, recurring reauthorizations of previous laws, and suggested recommendations made out of a significant number of educational commissions and summits, from the foundation of the American Republic to the eve of its enactment in 2002. Despite considerable efforts to address racial disparities, millions of American students, particularly blacks, continue to attend schools that are not separate but grossly unequal in both resources and academic outcomes. Thus, appraisal of the changing rate of segregation against black students throughout the different levels of the K-12 Education, both before and after the enactment of the No Child Left Behind Act, helps answer the question of whether the NCLB lived up to the promise of closing the black-white achievement gap.